Factors associated with non-compliance to tuberculosis treatment among patients in Gauteng Province, South Africa - Madumo, Serurubele Portia; Mathibe, Mmampedi; Hoque, Muhammad (Universitas Nahdlatul Ulama Surabaya, 2025)
Despite the implementation of several tuberculosis (TB) control initiatives, TB continues to be a significant cause of mortality and morbidity in South Africa primarily due to non-compliance with the recommended treatment. The objective of the study was to determine the frequency of non-compliance with treatment and identify the factors linked to non-compliance among tuberculosis patients in the Ekurhuleni South Health Sub-district in South Africa. This study was a quantitative cross-sectional analysis carried out on a sample of 309 patients, utilising an anonymous questionnaire. The data was analysed using Stata version 14. The findings indicated that those who had a sufficient food supply for a period beyond 6 months demonstrated a decreased likelihood of adhering to tuberculosis therapy (odds ratio = -0.12, p < 0.05). Additionally, the study revealed that those who had communicated with their family or friends about their tuberculosis treatment were more inclined to comply with the treatment regimen (OR=0.11; p<0.1). Individuals who were unmarried had a 22% lower likelihood of adhering to medication (OR=0.22; p<0.05). Based on these findings, initiatives designed to enhance adherence to TB treatment in Gauteng Province should implement a comprehensive approach, integrating economic assistance, focused education, and strategies to reduce stigma. Keywords: Alcohol consumption, scarcity of food, side effects, knowledge